Protection Of Children's Rights Within The Family - Abdul Majid, M. Kaprawi (IHSA Institute, 2024)
It is necessary for children to receive guidance and protection from parents, family, the government, and adults during their development in understanding the environment. Judging from various areas of life, children are not yet capable enough to protect themselves from actions that cause mental, physical, and psychological harm. Therefore, nowadays, considering the situation and conditions with the emergence of increasingly advanced technology, children need help from other people, especially from the family, to protect themselves. This research uses the library research method or literature study, namely reviewing data sources with references to books or articles, previous research journals, and other scientific writings related to the theme of this research. The research results show that the protection of children's rights in Islamic family law both in court (product of decisions and determinations) and outside of court (mediation) exists in two forms, namely hadhanah and guardianship